Effect of Watermelon Juice Consumption on Brachial Blood Pressure among Sudanese Hypertensive Patients - BabikerAli, Amna Abdalla (مجلة الجزيرة للعلوم الصحية; مجلد 12 عدد 2 (2016), 2016)
Abstract: Watermelon is a rich source of L-arginine and L-citrulline. L-arginine is the sole substrate of endothelial nitric oxide synthase (eNOS) producing nitric oxide (NO) and L-citrulline. NO is a vasodilator and muscle relaxant. L-arginine is also catabolized by arginase into L-ornithine and urea.The ratio of arginine to its catabolic products, L- citrulline and L-ornithine, accounts to its bioavailability. It has been reported that diminished global arginine bioavailability ratio (GABR) increases the risk of cardiovascular diseases and has been considered as a biomarker for coronary artery diseases. Encouraged by the seek of alternative non-pharmacological hypotensive agents, the effect of watermelon juice supplement was studied among 31 stage 1 hypertensive Sudanese patients. Exclusion criteria included pregnancy, metabolic diseases, diabetes, liver, kidney and cardiovascular diseases. Participants received one liter of freshly prepared watermelon juice daily for three weeks (L-citrulline/L-arginine:1g/0.5g per day). Results showed that watermelon juice supplement significantly increases plasma L-arginine, L-citrulline and L-ornithine levels and reduced brachial blood pressure and global arginine bioavailability ratio. In conclusion, we suggest that watermelon juice could be used as a potential natural hypotensive agent even at low doses. Although watermelon juice increases plasma arginine level, GABR may not be a useful biomarker to assess the progression of hypertension.